Impact of Supplier Development and Inventory Control on Supply Chain Effectiveness in Manufacturing Companies of Pakistan - Shakeel, Rida; Siddiqui, Danish Ahmed (ABC Journal of Advanced Research, 2019)
The purpose of this research is to study the impact of supplier development and inventory control on supply chain effectiveness in manufacturing companies of Pakistan. Self-administered questionnaires were used to collect data from the supply chain professionals working in different manufacturing companies of Pakistan. The study utilizes sample size of 200 and applying different statistical analysis such as Factor analysis, correlation and multiple regressions to check the hypothesis. The result indicates that supplier development and inventory control are significantly correlated with supply chain effectiveness. The result further explains that supplier development and inventory control have a significant and positive impact on supply chain effectiveness of manufacturing companies in Pakistan. Findings are helpful to supply chain practitioners and management in implementing a supply chain strategy that focuses on modern procurement procedures minimum use of inventory hence contributing in supply chain effectiveness. This will ultimately benefits the manufacturing companies in winning competitive advantage.